Claiming the Land: The Church Missionary Society and Architecture in the Arctic. (14th May 2018) - Turner, Emily
Abstract : The Arctic has claimed much interest in both popular discourse and academic scholarship, most notably concerning the voyages of Sir John Franklin. However, the explorers of the British Navy were not the only representatives of imperial expansion in what is now the Canadian Arctic. During the second half of the nineteenth century, the Church Missionary Society (CMS), the evangelical missionary society of the Church of England, undertook a substantial programme of evangelism throughout the region, not just aiming to convert indigenous people, but also to claim the land for the British empire and establish a strong presence in the region as an integral aspect of the providential expansion of empire. This article contends that the CMS attempted to achieve those aims through the creation of permanent infrastructure which brought the region into the fold of empire in a way that exploration could not, as missionaries used buildings to transform the land and its inhabitants as part of the duty of empire and its agents towards all its inhabitants. In claiming the land for empire, architecture was not just a by-product of occupation but rather a vital and integral agent in securing northern territories for God and empire.